TEORIA SOCIAL Y PSICOANALISIS EN TRANSICION: SUJETO Y SOCIEDAD DE FREUD A KRISTEVA - Elliott, Anthony (1995)
TRADUCCION DE: SOCIAL THEORY AND PSYCHOANALYSIS IN TRANSITION. SELF AND SOCIETY FROM FREUD TO KRISTEVA